Book of shadows : Blair Witch 2 [videorecording (DVD)] - Berlinger, Joe; Director, Kim; Donovan, Jeffrey; Leerhsen, Erica, 1976- (Artisan Home Entertainment, 2001)
After spending a night in the Black Hills of Burkittsville, Maryland, four young fans of the original Blair Witch movie descend into a nightmare realm of murder, madness and perception-bending supernatural horror.